Cystic Squamous Cell Carcinomas of the Jaws: Twelve Cases Highlighting Histopathological Pitfalls. (September 2020) - Barrett, Andrew W.; Garg, Montey; Armstrong, Daniel; Bisase, Brian S.; Newman, Lawrence; Norris, Paul M.; Shelley, Michael; Tighe, John V.; Hyde, Nicholas C.; Chaston, Nicola J.; Gulati, Aakshay
Cystic squamous cell carcinomas (SCCs) of the jaws, including carcinoma cuniculatum, are rare, slow growing, and relentlessly invasive. The aim of this article is to present 12 cases, 4 of which were designated as carcinoma cuniculatum on the basis of deeply endophytic, anastomosing channels of cystic stratified squamous epithelium and keratin microabscesses. The other 8 were also cystic, but more heterogeneous morphologically and were diagnosed as well differentiated SCCs. Six patients were female, 6 were male (mean age = 74.0 years, range = 50-94 years). Six tumors affected the mandible, 6 the maxillary alveolus with or without extension into the hard palate. All patients underwent primary resection with neck dissection and were staged as T4a N0 M0. In 4 patients, diagnosis was delayed as a result of superficial biopsies and/or confusing histopathology. Cystic SCCs of the jaws can be difficult to diagnose and clinicoradiological correlation is essential. Long-term follow-up is mandatory.